HUMAN INFRASTRUCTURE SECURITY - Candyce Kelshall (The Journal of Intelligence, Conflict and Warfare)
On November 19th, 2024, Adj. Prof. Candyce Kelshall presented Human Infrastructure Security for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were the notion of human infrastructure security and identity-wellbeing, the weapons used in soft and hybrid war, and the creation of new spectacle violence frameworks.